Childhood Character Building in Drama Script Mencari Taman by Noorca M. Massardi : A Literary Psychology Approach - Najma Murdhia; Wika Soviana Devi (IAIN Bengkulu, 2022)
Character building in children is important to help them have good characteristics and personalities. The characteristics of each child are also important and must be understood by parents to educate their children well. The purpose of this study was to describe the character building in children in the drama script